(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
This article analyzes the emergence of the Jadidist movement, its socio-political and educational essence, its developmental directions in the territories of Turkestan, Bukhara, and Khiva, as well as its main ideas and goals. Furthermore, the stages of the Jadidist movement, its press activities, and its historical significance are highlighted on a scientific basis.